Real-Time WebRTC based Mobile Surveillance System - Alistair Baretto; Noel Pudussery; Veerasai Subramaniam; Amroz Siddiqui (International Journal of Engineering and Management Research, 2021)
The rapid growth that has taken place in Computer Vision has been instrumental in driving the advancement of Image processing techniques and drawing inferences from them. Combined with the enormous capabilities that Deep Neural networks bring to the table, computers can be efficiently trained to automate the tasks and yield accurate and robust results quickly thus optimizing the process. Technological growth has enabled us to bring such computationally intensive tasks to lighter and lower-end mobile devices thus opening up a wide range of possibilities. WebRTC-the open-source web standard enables us to send multimedia-based data from peer to peer paving the way for Real-time Communication over the Web. With this project, we aim to build on one such opportunity that can enable us to perform custom object detection through an android based application installed on our mobile phones. Therefore, our problem statement is to be able to capture real-time feeds, perform custom object detection, generate inference results, and appropriately send intruder alerts when needed. To implement this, we propose a mobile-based over-the-cloud solution that can capitalize on the enormous and encouraging features of the YOLO algorithm and incorporate the functionalities of OpenCV’s DNN module for providing us with fast and correct inferences. Coupled with a good and intuitive UI, we can ensure ease of use of our application.